Long noncoding RNA GAS5 acts as a competitive endogenous RNA to regulate GSK-3β and PTEN expression by sponging miR-23b-3p in Alzheimer’s disease - Li Zeng; Kaiyue Zhao; Jianghong Liu; Mimin Liu; Zhongdi Cai; Ting Sun; Zhuorong Li; Rui Liu (Neural Regeneration Research)
Long noncoding RNA and microRNA are regulatory noncoding RNAs that are implicated in Alzheimer’s disease, but the role of long noncoding RNA-associated competitive endogenous RNA has not been fully elucidated. The long noncoding RNA growth arrest-specific 5 (GAS5) is a member of the 5′-terminal oligopyrimidine gene family that may be involved in neurological disorders, but its role in Alzheimer’s disease remains unclear. This study aimed to investigate the function of GAS5 and construct a GAS5-associated competitive endogenous RNA network comprising potential targets. RNA sequencing results showed that GAS5 was upregulated in five familial Alzheimer’s disease (5×FAD) mice, APPswe/PSEN1dE9 (APP/PS1) mice, Alzheimer’s disease-related APPswe cells, and serum from patients with Alzheimer’s disease. Functional experiments with targeted overexpression and silencing demonstrated that GAS5 played a role in cognitive dysfunction and multiple Alzheimer’s disease-associated pathologies, including tau hyperphosphorylation, amyloid-beta accumulation, and neuronal apoptosis. Mechanistic studies indicated that GAS5 acted as an endogenous sponge by competing for microRNA-23b-3p (miR-23b-3p) binding to regulate its targets glycogen synthase kinase 3beta (GSK-3β) and phosphatase and tensin homologue deleted on chromosome 10 (PTEN) expression in an Argonaute 2-induced RNA silencing complex (RISC)-dependent manner. GAS5 inhibited miR-23b-3p-mediated GSK-3β and PTEN cascades with a feedforward PTEN/protein kinase B (Akt)/GSK-3β linkage. Furthermore, recovery of GAS5/miR-23b-3p/GSK-3β/PTEN pathways relieved Alzheimer’s disease-like symptoms in vivo, indicated by the amelioration of spatial cognition, neuronal degeneration, amyloid-beta load, and tau phosphorylation. Together, these findings suggest that GAS5 promotes Alzheimer’s disease pathogenesis. This study establishes the functional convergence of the GAS5/miR-23b-3p/GSK-3β/PTEN pathway on multiple pathologies, suggesting a candidate therapeutic target in Alzheimer’s disease.